Studi Fenomenologi UKM Kerajinan Tangan Berbasis Limbah Kayu pada D&D Craft (Purbalingga) dan Jk Watch (Yogyakarta) - Simamora, Virgo; Mulyani, Shindi Sri; Pravitasari, Endyastuti (Ekonomis: Journal of Economics and Business, 2025)
This study is a phenomenological study that focuses on wood waste-based innovation carried out by handicraft SMEs in Purbalingga and Yogyakarta. The data collection technique used is purposive sampling technique with the criteria being SMEs that have exported products and received assistance from government agencies. The results of this study indicate that innovation capability is an important capability possessed by handicraft SMEs that determines the sustainability of their business in the wood waste-based handicraft industry. To improve innovation capability, SMEs need to be given continuous training.